Domingo Faustino Sarmiento’s Birth House: A Case of Domestic Architecture in Colonial San Juan, Argentina - Igareta, Ana (Universidad ORT Uruguay, 2020)
Little has been written in Argentinian archeology architecture materials and techniques used at western provinces of the country during the colonial period. In the case of the city of San Juan, part of Chilean Governorate for over two centuries, there are no history of direct analysis of buildings or remains of colonial buildings. The current Museo y Biblioteca Casa Natal de Sarmiento is one of the few late colonial buildings still remain standing in the city and its analysis from an archaeological perspective was considered a valuable opportunity. This article presents the preliminary results obtained during the construction of a database that gathers all the mentions identified in documentary, historical and bibliographic sources, regarding raw materials, techniques and systems used in the construction of the house and further interventions.